Analisis Segmentasi Konsumen Warunk AIUEO Di Kota Bandung Dengan Analisis Faktor Dan Analisis Cluster - Syarah Rizkia Feriaty; Wulan Rosmeinasari (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Warunk AIUEO is a place to eat that provides menus are usually served by food stalls. This restaurant usually crowded with young people, provides main menus such as noodles, bread, and various kinds of rice. Warunk AIUEO established since 2014, is able to increase fast food noodles but still at affordable prices. Therefore, this study aims to see what factors motivate consumers to visit this place based on the profile characteristics of consumers. This study used questionnaire as a tool for data collection, respondents are limited who live in Bandung. The number of respondents in this study amounted to 40 respondents. The variables in the questionnaire are 14 manifest variables which are processed using factor analysis to reduce the number of variables to 3 factors which represent the 14 initial variables. These three factors are reliability, assurance, and serviceability. The results of the factor analysis are then used to input cluster analysis data, which aims to group respondents based on their characteristics when deciding to visit Warunk AIUEO. Cluster analysis shows that 3 clusters are formed which are labeled modern, functional, and simple.